2009
DOI: 10.1002/cncr.24150
|View full text |Cite
|
Sign up to set email alerts
|

Injuries to inferior vermis and dentate nuclei predict poor neurological and neuropsychological outcome in children with malignant posterior fossa tumors

Abstract: Formal properties of ensemble density functionals are examined. Expressions for the difference between energy functionals where the particle number differs by one are constructed in terms of their first functional derivatives for the universal energy functional, the electron–electron repulsion energy functional, and the interacting kinetic energy functional. Equations that must be satisfied by second and higher order functional derivatives are derived. It is also shown that the shape of ${\delta V_{ee}[\rho]\o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 62 publications
6
62
1
1
Order By: Relevance
“…The traditional approach for removing ependymomas of the fourth ventricle is incision of the cerebellar vermis, which, however, is often associated with a higher incidence of cerebellar mutism or posterior fossa syndrome, along with chronic neurocognitive sequelae, compared with the trans-CMF appr oach (13,(18)(19)(20)(21)24,25,(41)(42)(43). The trans-CMF approach to the fourth ventricle, which does not cause significant injury to the neural tissue, was first proposed by Matsushima et al (36), and is currently widely accepted (8,13,14,(18)(19)(20)(22)(23)(24)(25)(26)(29)(30)(31)(32)36,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional approach for removing ependymomas of the fourth ventricle is incision of the cerebellar vermis, which, however, is often associated with a higher incidence of cerebellar mutism or posterior fossa syndrome, along with chronic neurocognitive sequelae, compared with the trans-CMF appr oach (13,(18)(19)(20)(21)24,25,(41)(42)(43). The trans-CMF approach to the fourth ventricle, which does not cause significant injury to the neural tissue, was first proposed by Matsushima et al (36), and is currently widely accepted (8,13,14,(18)(19)(20)(22)(23)(24)(25)(26)(29)(30)(31)(32)36,43).…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing literature (19,29), the bilateral trans-CMF approach appears to be associated with a high rate of postoperative mutism, compared with the unilateral approach. Despite the controversy surrounding the pathophysiological mechanisms, it is considered that the dentate nuclei and their connections with the thalamus through the brainstem participate in speech function; therefore injury to this pathway may result in mutism (12,14,20,21). Another explanation for this observation may be that the preservation of the contralateral CMF reduces the likelihood of blood vessel injury (particularly in branches of the PICA) during the unilateral approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Frassanito et al 31 reported a case of CM after spontaneous intratumoral bleeding involving the upper cerebellar vermis and believed that the localization of bleeding provided confirmation of the role played by the upper vermis in speech control. Puget et al 78 found that persistent clinical cerebellar signs or fine motor dexterity impairment was significantly related to the extent of injury (pre-or postsurgical) to both the inferior vermis and the dentate nuclei. Animal models were also used, and a recent study found that juvenile rats that had vermian splitting operations showed deficient social behavior and vocalization postoperatively, compared with sham-lesioned rats and healthy controls.…”
Section: Pathophysiologymentioning
confidence: 99%
“…En el mutismo cerebeloso y en el síndrome de mutismo cerebeloso el sustrato anatómico más citado en la literatura tiene relación con el núcleo dentado y el tracto dento-rubro-talámico [17][18][19][20][21][22][23] .…”
Section: Introductionunclassified